2016
DOI: 10.3389/fnins.2016.00516
|View full text |Cite
|
Sign up to set email alerts
|

ASD and Genetic Associations with Receptors for Oxytocin and Vasopressin—AVPR1A, AVPR1B, and OXTR

Abstract: Background: There are limited treatments available for autism spectrum disorder (ASD). Studies have reported significant associations between the receptor genes of oxytocin (OT) and vasopressin (AVP) and ASD diagnosis, as well as ASD-related phenotypes. Researchers have also found the manipulation of these systems affects social and repetitive behaviors, core characteristics of ASD. Consequently, research involving the oxytocin/vasopressin pathways as intervention targets has increased. Therefore, further exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 79 publications
(115 reference statements)
3
42
0
Order By: Relevance
“…Carriers of the MHS C allele displayed more stress-related vocal symptoms (dysphonia, muscle tension, frequency changes) and higher cortisol levels 62 . The MHS allele rs2258493(T) has been linked to ASD subphenotypes 63 and diagnosi 41, 64, 65 , negative scores in social performance, perception and mentalizing tasks in schizophrenia patients 66 , ADHD patients 67 and depressive temperament (as part of a haplotype block) 19 . Carriers of this allele also showed reduced mesolimbic reward system activation, a result that might point towards the neurobiological basis of the aforementioned phenotypic effects of this SNP 68 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Carriers of the MHS C allele displayed more stress-related vocal symptoms (dysphonia, muscle tension, frequency changes) and higher cortisol levels 62 . The MHS allele rs2258493(T) has been linked to ASD subphenotypes 63 and diagnosi 41, 64, 65 , negative scores in social performance, perception and mentalizing tasks in schizophrenia patients 66 , ADHD patients 67 and depressive temperament (as part of a haplotype block) 19 . Carriers of this allele also showed reduced mesolimbic reward system activation, a result that might point towards the neurobiological basis of the aforementioned phenotypic effects of this SNP 68 .…”
Section: Resultsmentioning
confidence: 99%
“…Concerning AVPR1B, rs28676508(T) has been claimed to be involved in child onset aggression 94 . The missense (arginine to histidine, position 364) variant rs28632197(T) has been associated with ASD diagnosis 63 and panic disorder 95 . Finally, the G allele of rs33985287 protects against depressive moods in female children 96 .…”
Section: Resultsmentioning
confidence: 99%
“…Recent data indicate that variation in Avpr1b signaling may have maladaptive impacts on human social behavior. Avpr1b SNP variants are positively correlated with autism diagnoses (Francis, Kim et al 2016) and with increased emotional aggression (Luppino, Moul et al 2014). Similarly, life-long disruption of Avpr1b signaling through genetic removal in knockout (KO) mice results in altered social aggression and social memory performance (Wersinger, Ginns et al 2002), while leaving spatial and object memory performance and olfactory discrimination intact, indicating a special role in the social aspect of memory (Wersinger, Ginns et al 2002, Wersinger, Kelliher et al 2004, Wersinger, Caldwell et al 2007, Caldwell, Wersinger et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The involvement of DNA methylation in regulating the expression of OXTR has been suggested, but the exact mechanism mediating this process remains largely unknown (9)(10)(11). Epigenetic studies in humans have found altered DNA methylation in the 5′ CpG island of OXTR in a wide spectrum of morbid behaviors and neuropsychiatric disorders, such as autism spectrum disorder (ASD), schizophrenia, bipolar, depression, obsessive-compulsive disorders (OCD), and anxiety (12)(13)(14)(15)(16)(17)(18). Similar correlations between DNA methylation and behavior are also reported in other species, such as dog and nonhuman primates (19,20).…”
Section: Introductionmentioning
confidence: 99%